Behavioral Study of Data Structures on Lempel Ziv Welch (LZW) Data Compression Algorithm and ITS Computational Complexity - Nishad, P. M.; Chezian, R. Manika (2014 International Conference on Intelligent Computing Applications, 2014)
LZW (Lempel Ziv Welch) compression is the first widely used universal data compression method on computers. After the invention of LZW there are lots of improvements and enhancement done on LZW in order to improve the compression ratio and reduce the computational complexity. LZW is very effective on the files containing lots of repetitive data especially for text and monochrome images. The LZW algorithm uses dictionary while decoding and encoding. The computational and space complexity of LZW data compression algorithm is purely depends on the effective implementation of data structure. A space efficient implementation of dictionary with data structure is most important. The data structure implementation must give better performance on the following operation: insertion of new pattern to the dictionary, searching of a given pattern and returning the matching code word if it is present in the dictionary as a phrase. This paper analyses a number of data structures commonly employed in the LZW dictionary based compression and decompression.